(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This study tackles the contribution of the environmental audit in achieving the sustainability of the environmental balance in the Sudanese business environment. The study aimed at clarifying the role of environmental auditing in supporting sustainable development, and to recognize the role of environmental audit in urging businesses to abide by environmental protection. It also shows how effective the environmental audit reports are, in providing the reliable data for the concerned authorities, in order to use it in making the decisions that would help in the sustainability of the environmental balance. To achieve the goals of the study, a questionnaire was developed and distributed to the registered chartered accountants in Sudan. The study sample consisted of (152) participants. The main findings of the study were that: there is considerable consensus among chartered accountants in Sudan on the impact of environmental audit reports in urging business organizations to protect and maintain the environment. Also, the environmental audit information has an important impact in providing reliable data for the concerned authorities. Finally, the environmental audit reports contribute in achieving the sustainability of environmental balance by providing quality data that would boost wise decisions.